2007
DOI: 10.1002/ange.200703443
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Symmetry Breaking by Chemically Manipulating Statistical Fluctuation in Crystallization

Abstract: Auf Biegen und Brechen: Ein Bruch der chiralen Symmetrie bei der Kristallisation intrinsisch chiraler, helicaler Koordinationspolymere gelingt durch die Einführung eines relativ stabilen Intermediats zur chemischen Steuerung der Keimbildungsgeschwindigkeit. Je weniger Kristallcluster gebildet werden, umso stärker ausgeprägt ist die Symmetriebrechung (siehe Bild).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 52 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…There are two families of refcodes within the qzd MOF cluster: LIWDEB (13 occurrences) and UKUVOL (21 occurrences). 58,59 All of these structures are one of two isomers of [{Cu(succinate)(4,4bipyridine)} n ], isolated under different experimental conditions, and thus could be considered duplicates. The high geometric similarity between duplicates relative to the similarity between other structures in the dataset skews the representation towards creating an isolated cluster.…”
Section: Embedding Schemesmentioning
confidence: 99%
“…There are two families of refcodes within the qzd MOF cluster: LIWDEB (13 occurrences) and UKUVOL (21 occurrences). 58,59 All of these structures are one of two isomers of [{Cu(succinate)(4,4bipyridine)} n ], isolated under different experimental conditions, and thus could be considered duplicates. The high geometric similarity between duplicates relative to the similarity between other structures in the dataset skews the representation towards creating an isolated cluster.…”
Section: Embedding Schemesmentioning
confidence: 99%
“…This phenomenon indicated that the preferred handedness of aggregates was governed by chance, not by any possible external chiral impurities in the system. 39,50 We then tested the heating temperature on the self-assembly of OPV 3 -b-PEG 17 in the mixture of water/ethanol (v/v = 1/1). OPV 3 -b-PEG 17 solution samples (0.1 mg/mL) were heated at 40, 55, and 70 °C, respectively, for 1 h followed by aging at room temperature (23 °C) for 48 h. Irregular platelets were formed upon heating at 40 °C and the solution showed very weak Cotton effect (Figure 3A,D).…”
Section: Different Conditionsmentioning
confidence: 99%
“…At the initial stage of the formation of aggregates driven by π−π stacking of OPV 3 segments accompanying with possible steric repulsion between solvated PEG domains, the occurrence of statistical fluctuations in the orientation of ordered packing of OPV 3 blocks could lead to an accidental excess of helical or/and twisted structures. 39,50 Because of the strong directional interaction deriving from π−π stacking between OPV 3 segments, the growth of aggregates by addition of free OPV 3 -b-PEG 17 onto the ends of existed helical or twisted "seeds" of aggregates preferred to follow the same direction. 52 Besides, once a certain helical sense excess exists, the newly formed aggregates might follow the same direction, rather than opposite helical or twisted direction, by chiral autocatalysis.…”
Section: Different Conditionsmentioning
confidence: 99%
“…24−29 The spontaneous resolution of chiral MOFs from achiral precursors usually results in conglomerates, i.e., a mixture of homochiral crystals having opposite handedness. 30 However, the generation of homochirality from achiral precursors is still unpredictable. Various factors such as coordination around the metal center, selection of the ligands, and host−guest interactions and stacking interactions can maneuver the formation of chiral MOFs from achiral building blocks.…”
Section: ■ Introductionmentioning
confidence: 99%